Twice-yearly Depemokimab in severe asthma with an eosinophilic phenotype - Jackson, David; Wechsler, Michael E.; Jackson, Daniel J.; Bernstein, David; Korn, Stephanie; Pfeffer, Paul E.; Chen, Ruchong; Saito, Junpei; Martinez, Gustavo de Luíz; Dymek, Lucyna; Jacques, Loretta; Bird, Nicholas; et al. (The New England journal of medicine, 2024)
Depemokimab is an ultra-long-acting biologic therapy with enhanced binding affinity for interleukin-5 that may enable effective 6-month dosing intervals. METHODS: In these phase 3A, randomized, placebo-controlled replicate trials, we evaluated the efficacy and safety of depemokimab in patients with severe asthma and an eosinophilic phenotype characterized by a high eosinophil count (≥300 cells per microliter in the previous 12 months or ≥150 cells per microliter at screening) and a history of exacerbations despite the receipt of medium- or high-dose inhaled glucocorticoids. Patients were randomly assigned in a 2:1 ratio to receive either depemokimab (at a dose of 100 mg subcutaneously) or placebo at weeks 0 and 26, plus standard care. The primary end point was the annualized rate of exacerbations at 52 weeks. Secondary end points, which were analyzed in a hierarchical manner to adjust for multiplicity, included the change from baseline in the score on the St. George’s Respiratory Questionnaire (SGRQ), the forced expiratory volume in 1 second, and asthma symptom reports at 52 weeks. RESULTS: Across the two trials, 792 patients underwent randomization and 762 were included in the full analysis; 502 were assigned to receive depemokimab and 260 to receive placebo. The annualized rate of exacerbations was 0.46 (95% confidence interval [CI]), 0.36 to 0.58) with depemokimab and 1.11 (95% CI, 0.86 to 1.43) with placebo (rate ratio, 0.42; 95% CI, 0.30 to 0.59; P<0.001) in SWIFT-1 and 0.56 (95% CI, 0.44 to 0.70) with depemokimab and 1.08 (95% CI, 0.83 to 1.41) with placebo (rate ratio, 0.52; 95% CI, 0.36 to 0.73; P<0.001) in SWIFT-2. No significant betweengroup difference in the change from baseline in the SGRQ score was observed in either trial, so no statistical inference was drawn on subsequent secondary end points. The proportion of patients with any adverse event was similar in the two groups in both trials. CONCLUSIONS: Depemokimab reduced the annualized rate of exacerbations among patients with severe asthma with an eosinophilic phenotype. (Funded by GSK; SWIFT-1 and SWIFT-2 ClinicalTrials.gov numbers, NCT04719832 and NCT04718103.)
Veröffentlicht: September 9, 2024
Gesehen am 05.08.2025